2022
DOI: 10.1093/cid/ciac031
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Severe Acute Respiratory Syndrome Coronavirus 2 Among Incarcerated Adult Men in Quebec, Canada, 2021

Abstract: Background People in prison are at increased risk of SARS-CoV-2 infection due to overcrowding and challenges in implementing infection prevention and control measures. We examined the seroprevalence of SARS-CoV-2 and associated carceral risk factors among incarcerated adult men in Quebec, Canada. Methods We conducted a cross-sectional seroprevalence study in 2021 in three provincial prisons, representing 45% of Quebec’s incar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…In concordance with previous accounts of under-testing in prisons and jails ( 25 – 28 ), this study revealed substantial undetected COVID-19 infection among both residents and staff. These results are consistent with other studies employing antibody testing in carceral ( 31 ) and non-carceral settings ( 30 , 59 ). We also found a significant association between antibody positivity and perceived likelihood of prior infection among residents without a prior COVID-19 diagnosis, suggesting that the hidden burden of infection was concentrated among individuals who were aware of exposure or infection but had not been tested.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concordance with previous accounts of under-testing in prisons and jails ( 25 – 28 ), this study revealed substantial undetected COVID-19 infection among both residents and staff. These results are consistent with other studies employing antibody testing in carceral ( 31 ) and non-carceral settings ( 30 , 59 ). We also found a significant association between antibody positivity and perceived likelihood of prior infection among residents without a prior COVID-19 diagnosis, suggesting that the hidden burden of infection was concentrated among individuals who were aware of exposure or infection but had not been tested.…”
Section: Discussionsupporting
confidence: 92%
“…Antibody testing, which can identify prior infection by detecting antibodies to SARS-CoV-2 in the blood, is one strategy to assess the extent of undetected infection in a population and to determine factors associated with risk of prior infection ( 29 , 30 ). However, to our knowledge few studies–none in the U.S.–have employed antibody testing in a carceral setting ( 31 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, each prison has a variable number of correctional workers and incarcerated individuals, and is different in size and spatial organization, further impacting differences in seroprevalence. This variability was also observed during our preceding seroprevalence study among incarcerated individuals at the same three sites (27% at EDM, 19% at EDSJ, and 15% at EDRDP) (3). Very few studies exploring the risk of infectious diseases in correctional settings have focused on correctional workers despite having shared health and safety hazards as those incarcerated (36).…”
Section: Discussionsupporting
confidence: 57%
“…Canadian correctional facilities have witnessed many large outbreaks of the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) since the beginning of the pandemic, affecting both incarcerated individuals and correctional workers alike (1,2). Several studies have demonstrated that COVID-19 case rates among incarcerated individuals and correctional workers constantly exceeded those of surrounding communities during the pandemic (3)(4)(5)(6), underscoring the prison environment as particularly conducive to SARS-CoV-2 transmission. Correctional workers have experienced many of the same infrastructural catalysts to SARS-CoV-2 transmission as individuals in prison, including inadequate ventilation, unhygienic conditions, and difficulties in accessing and implementing effective infection prevention and control measures (7)(8)(9)(10)(11) -occupational risks that are further heightened by daily community exposures.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to a seropositivity rate (22%) reported among 1100 incarcerated men in Canada, which was attributed to enhanced daily interactions in a congregate setting. 25 …”
Section: Discussionmentioning
confidence: 99%